Climate risks and agricultural changes in conflict-affected Myanmar - Minten, Bart; van Asselt, Joanna; Aung, Zin Wai; Goeb, Joseph (International Food Policy Research Institute, 2025)
Climate change and conflict are increasingly shaping livelihoods in Myanmar, with agricultural households among the most directly affected. Yet, empirical evidence on how these stressors affect farmers’ adaptation strategies and agricultural assets remains limited. We draw on unique largescale primary surveys: Over a three-year period, we conducted bi-annual surveys with nearly 5,000 farmers, collecting data on exposure to conflict, natural risks, climate change perceptions, agricultural adaptation, and agricultural land valuation.